Comparative evaluation of collection varieties of winter garlic by yield - V. V. Skorina; I. G. Kakhtsiankova (Овощи России)
Relevance. To produce garlic for use both in the domestic and foreign markets, there is no required number of high-yielding varieties with large onions and a small number of cloves, as well as resistant to new growing conditions. In selection with a culture of garlic, in addition to zoned varieties, it is advisable to use local improved forms, however, the morphobiological characteristics of garlic can change depending on the growing conditions and, as a result, plants can die, reduce resistance, productivity and quality indicators, which depend on the breeding and genetic characteristics of the variety.Methods. The research was carried out on the experimental field of the Department of Horticulture, UO BSAA. The 67 samples of winter garlic were studied. The collection material consisted of varieties and clones that were selected from six regions of Belarus. The Belovezhsky variety was used as a control.Results. According to the results of the studies, the best in terms of bulb weight, number of cloves in the bulb, clove weight and yield were selected samples – AM1–18, OR3–18, OP5–18, MM1–18, UG–18, ЮM1–18, 2000–18, MГ1–18, DM–18, MГ4–18, varieties Agaton, Antonik, Gorets, Soyuz, Junior.